Determining the Prevalence of Sleep Disorder and Its Predictors Among Elderly Residents of Nursing Homes of Ahvaz City in 2017 - Shahab Papi; Zeynab Karimi; Gholamreza Ghaed Amini Harooni; Azadeh Nazarpour; Parvin Shahry (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives Sleep quality is an important indicator of many geriatric diseases. As people age, changes happen in the quality and quantity of their sleep, which means sleep disorders and complications. This study aimed to determine the predictors of sleep disorder in elderly people living in nursing homes. Methods & Materials This cross-sectional study was carried out on a sample of 130 elderly residents of senior care homes in Ahvaz City, Iran. The samples were selected by the convinience sampling method and according to inclusion and exclusion criteria. Pittsburgh sleep quality questionnaire, general health questionnaire (12 questions form), knee pain questionnaire, social support questionnaire, and demographic characteristic checklist were used to collect the study data that were analyzed using stepwise linear regression analysis in SPSS22. Results In this study, 33.8% (n=44) of the participants were men and 66.2% (n=86) were women. The Mean±SD age of the subjects was 68±7.8 years. In total, 13.8% of the samples had a low level of sleep disorder, 81.5% moderate level of sleep disorder, and 4.6% severe level of sleep disorder. Based on the fitted regression model (F=7.24; P<0.001), multiple diseases (β=0.20), perceived social support (β= -0.26), joint stiffness (β=0.25), and knee pain (β = 0.24) were the significant predictors of sleep disorder in the elderly people, and explained 18.9% of the changes in sleep quality. Conclusion The results of the study showed that 86.1% of the elderly had a sleep disorder. Perceived social support, joint stiffness, knee pain, and multiple diseases were among determinants and predictors of elderly sleep disorder.